2018
DOI: 10.1108/caer-04-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Price transmission, reserve regulation and price volatility

Abstract: Purpose The purpose of this paper is to examine whether Chinese pork reserve regulation policy fulfills its function in stabilizing market prices and simultaneously to theoretically and empirically analyze the causes leading to the failure of Chinese Government’s intervention in the market, especially in the context of asymmetric pork and hog price information transmission. Design/methodology/approach A modified Reserve-Cobweb model based on the competitive storage model developed by Muth in 1961 is employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Tan and Zeng [1] found that although the reserve spider web model provides theoretical insights, it shows that the government's implementation of reserve policy tools to control price volatility will increase price volatility. Still, the empirical results show that the policy induces high correction and increases price volatility, especially in the asymmetric transmission of price information.…”
Section: Research On the Control Policy Of Pig Pricementioning
confidence: 99%
See 1 more Smart Citation
“…Tan and Zeng [1] found that although the reserve spider web model provides theoretical insights, it shows that the government's implementation of reserve policy tools to control price volatility will increase price volatility. Still, the empirical results show that the policy induces high correction and increases price volatility, especially in the asymmetric transmission of price information.…”
Section: Research On the Control Policy Of Pig Pricementioning
confidence: 99%
“…Still, the empirical results show that the policy induces high correction and increases price volatility, especially in the asymmetric transmission of price information. Therefore, the Chinese government should reduce excessive intervention in pork prices and let the market play a role in the pig and pork market [1]. By decomposing the structure of the pig supply chain, Lu et al [2] constructed a dynamic model of the pig industry system and found that reducing pig breeding cost is the most effective long-term strategy to stabilize pig price.…”
Section: Research On the Control Policy Of Pig Pricementioning
confidence: 99%
“…Cobweb theorem based on pig cycle theory is still widely used as the analytic tool in recent economic studies [61][62][63] . According to the pig cycle theory in economics, cyclical fluctuations are normal for agricultural commodities with long time lags from breeding decisions to output for sale 64 .…”
Section: Supply and Pricementioning
confidence: 99%
“…Government storage is supposed to help the supply and expectations and thus reduce dramatic price fluctuations 72 . The competitive storage model is frequently used for analyses 63,72 . To analyze the market effects of government emergency pork reserves, this study adopts the analytic paradigm of augmented Competitive Storage model proposed by Tan&Zeng (2018).…”
Section: Government Frozen Pork Reserve Effectsmentioning
confidence: 99%
See 1 more Smart Citation